A contribution to the critique of the political economy of Brazilian psychiatric counter-reforms - Antunes da Costa, Pedro Henrique; Mendes, Kíssila Teixeira (Argumentum, 2020)
This article outlines a critique of the political economy of current Brazilian Psychiatric Counter-reform. It relies on studies on the political economy of Psychiatric Reform, budgetary data, and the implementation of mental healthcare policies from 2001 to 2019. Psychiatric Counter-reform is a process of budgetary downsizing, renewed use of asylums, and commodification, with: the reappearance of psychiatric hospitals in policies, the centrality of Therapeutic Communities in the area of alcohol and other drugs, increases in the funding of such institutions, the reversal of the tendency to close psychiatric beds and reduced investment in extra-hospital actions. This constitutes a break in the continuous development of Psychiatric Reform; an expression of neoliberal dynamics in mental healthcare, which has intensified since 2015, expanding the expropriation and plundering of both the working class and the State by capital.